Molecular Detection Challenges of Human Plasmodium Knowlesi Infection by Polymerase Chain Reaction and Sequencing - Erma Sulistyaningsih; Resy Metri Belizani; Irawan Fajar Kusuma; Sahrir Sillehu; Rosita Dewi (Faculty of Medicine, Universitas Diponegoro, 2023)
Background: Plasmodium knowlesi is the fifth Plasmodium sp. causing malaria in human. There are 545 P. knowlesi malaria cases were reported in Indonesia in 2010-2021, the first cases were reported from South Kalimantan and more cases were occurred in Sumatra island. The morphology of P. knowlesi is difficult to distinguish from other Plasmodium species, it is similar to P. falciparum and P. malariae. Therefore, molecular identification is still the most promising method for diagnosing P. knowlesi infection.Objective: This study aimed to analyze the molecular detection method of human P. knowlesi infection using Polymerase Chain Reaction (PCR) and sequencing techniques.Methods: DNA was isolated from malaria blood samples. P. knowlesi detection was conducted by nested PCR using primer rPLU1 and rPLU5 for nested 1 and Kn1f and Kn3r for nested 2. The PCR products were directly sequencing. The sequences were analysed using Basic Local Alignment Search Tool (BLAST) in the National Center for Biotechnology Information (NCBI).Results: Ten blood sample of malaria patients from Maluku province were collected after informed consent. The P. knowlesi specific PCR amplification resulted band of approximately 420 bp in all samples. Sequence analysis showed the highest similarity (89-92 %) with many global P. falciparum strains. However, BLAST analysis for part of sequences also showed high similarities with several P. knowlesi H strains 18s rRNA from Peninsular Malaysia. Primer analysis using BLAST demonstrated the specificity of kn3r-nested 2 primer, however, kn1f primer showed a cross reactive with Plasmodium sp including P. falciparum, P. knowlesi, and P. vivax.Conclusion: A new primer design with higher specificity for human P. knowlesi detection was needed to develop.